Blueprint Report Zhyper Sdn Bhd "Hyper Grabber” / Mohamed Zuheel Zaid - Zaid, Mohamed Zuheel (2020)
Our company provides people with a grabber tools called hyper grabber especially for those who often do the works that requires picking object on the floor and people that have difficulties to take object from narrow and dark place. Hyper grabber can help people picking object on the floor by extending the shaft of the grabber and pick it easily. This product has torchlight in front that can help the user to pick object in the dark and magnetic tip to help collect small metal objects. Hyper grabber also has switch to control the shaft and to control the torchlight and the switch’s battery also chargeable and changeable